Executive abilities in children with congenital visual impairment in mid-childhood. Issue 2 (17th February 2018) - Bathelt, Joe; de Haan, Michelle; Salt, Alison; Dale, Naomi Jane
ABSTRACT: The role of vision and vision deprivation in the development of executive function (EF) abilities in childhood is little understood; aspects of EF such as initiative, attention orienting, inhibition, planning and performance monitoring are often measured through visual tasks. Studying the development and integrity of EF abilities in children with congenital visual impairment (VI) may provide important insights into the development of EF and also its possible relationship with vision and non-visual senses. The current study investigates non-visual EF abilities in 18 school-age children of average verbal intelligence with VI of differing levels of severity arising from congenital disorders affecting the eye, retina, or anterior optic nerve. Standard auditory neuropsychological assessments of sustained and divided attention, phonemic, semantic and switching verbal fluency, verbal working memory, and ratings of everyday executive abilities by parents were undertaken. Executive skills were compared to age-matched typically-sighted (TS) typically-developing children and across levels of vision (mild to moderate VI [MVI] or severe to profound VI [SPVI]). The results do not indicate significant differences or deficits on direct assessments of verbal and auditory EF between the groups. However, parent ratings suggest difficulties with everyday executive abilities, with the greatest difficulties in those with SPVI. The findings are discussed as possibly reflecting increased demands of behavioral executive skills for children with VI in everyday situations despite auditory and verbal EF abilities in the typical range for their age. These findings have potential implications for clinical and educational practices.